THE IMPORTANCE OF READING IN DEVELOPING INNOVATIVE THINKING YOUNG PEOPLE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article describes the socio-philosophical point of view of the author on the problems of the development of reading culture, which is considered relevant in modern society, and an attempt is made to objectively analyze the state of the processes of the role of libraries and new information technologies in the development of reading culture among young people. The importance of formation and development of reading culture among young people is emphasized. Opinions on the importance of libraries and new information technologies are presented.